Confounding factors of the expression of mTBI biomarkers, S100B, GFAP and UCH-L1 in an aging population - Emma Calluy; Charlotte Beaudart; Majed S. Alokail; Nasser M. Al‐Daghri; Olivier Bruyère; Jean‐Yves Reginster; Étienne Cavalier; Aurélie Ladang (2024)
Abstract Objectives To evaluate some confounding factors that influence the concentrations of S100 calcium binding protein B (S100B), glial fibrillary acidic protein (GFAP), and ubiquitin carboxyl-terminal hydrolase L-1 (UCH-L1) in older individuals. Indeed, recent guidelines have proposed the combined use of S100B and the “GFAP-UCH-L1” mTBI test to rule out mild traumatic brain injuries (mTBI). As older adults are the most at risk of mTBI, it is particularly important to understand the confounding factors of those mTBI rule-out biomarkers in aging population. Methods The protein S100B and the “GFAP and UCH-L1” mTBI test were measured using Liaison XL (Diasorin) and Alinity I (Abbott), respectively, in 330 and 341 individuals with non-suspected mTBI from the SarcoPhAge cohort. Results S100B, GFAP and UCH-L1 were all significantly correlated with renal function whereas alcohol consumption, Geriatric Depression Score (GDS), smoking habits and anticoagulant intake were not associated with any of these three biomarkers. Body mass index (BMI) and age were associated with GFAP and UCH-L1 expression while sex and mini-mental state examination (MMSE) were only associated with GFAP. According to the manufacturer’s cut-offs for mTBI rule-out, only 5.5 % of participants were positive for S100B whereas 66.9 % were positive for the “GFAP-UCH-L1” mTBI test. All positive “GFAP-UCH-L1” mTBI tests were GFAP+/UCH-L1-. Among individuals with cystatin C>1.55 mg/L, 25 % were positive for S100B while 90 % were positive for the mTBI test. Conclusions Our data show that confounding factors have different impacts on the positivity rate of the “GFAP-UCH-L1” mTBI test compared to S100B.